Anti-Inflammatory (M2) Response Is Induced by a sp2-Iminosugar Glycolipid Sulfoxide in Diabetic Retinopathy - Cano-Cano, Fátima; Alcalde-Estévez, Elena; Gómez-Jaramillo, Laura; Iturregui, Marta; Sánchez-Fernández, Elena M.; García Fernández, José M.; Ortiz Mellet, Carmen; Campos-Caro, Antonio; López-Tinoco, Cristina; Aguilar-Diosdado, Manuel; Valverde, Ángela M.; Arroba, Ana I. (Frontiers in Immunology, 2021)
Diabetic retinopathy (DR) is one of the most frequent complications of Diabetes Mellitus (DM) and is directly associated with inflammatory processes. Currently, neuro-inflammation is considered an early event in DR and proceeds via microglia polarization. A hallmark of DR is the presence of retinal reactive gliosis. Here we report the beneficial effect of (SS,1R)-1-docecylsulfiny-5N,6O-oxomethylidenenojirimycin ((Ss)-DS-ONJ), a member of the sp2-iminosugar glycolipid (sp2-IGL) family, by decreasing iNOS and inflammasome activation in BV.2 microglial cells exposed to pro-inflammatory stimuli. Moreover, pretreatment with (Ss)-DS-ONJ increased heme-oxygenase (HO)-1 as well as interleukin 10 (IL10) expression in LPS-stimulated microglial cells, thereby promoting M2 (anti-inflammatory) response by the induction of arginase-1. The results strongly suggest that this is the likely molecular mechanism involved in the anti-inflammatory effects of (SS)-DS-ONJ in microglia. (SS)-DS-ONJ further reduced gliosis in retinal explants from type 1 diabetic BB rats, which is consistent with the enhanced M2 response. In conclusion, targeting microglia polarization dynamics in M2 status by compounds with anti-inflammatory activities offers promising therapeutic interventions at early stages of DR.